The challenges of implementing distance education in Uganda: A case study - Gudula Naiga Basaza (Athabasca University Press, 2010)
This brief case study provides a pithy introduction to Uganda and outlines key factors that affect the implementation of distance education in the nation: poor infrastructure, the high cost of an education, an outdated curriculum, inadequate expertise in distance education, and poor attitudes towards distance learning. These factors are also evident in other African countries.